Propagation of Bambusa vulgaris-its Scope in Forestry - Khan, M. A. Waheed (Indian Forester, 1972)
Bamboo plantations are being raised increasingly. In this context, Bambusa vulgaris is of prime importance, as it is thorn-less, capable of high productivity and could be relled on culmcuttings for raising plantations. On the basis of experimental evidence, the technique of raising B. vulgaris plantations through culm-cuttings is described. Two-noded cuttings are made from middle one-thirds of the culm, and three-noded cuttings from the rest of the culm. On the onset of the rains, they are planted at 45 cm Ã— 45 cm spacement in nursery beds with heavy soil and flood irrigated at fortnightly intervals. By the middle of the following rainy season, they are well-established and fairly grown for planting out. They are planted out at 12 m Ã— 12 m spacement. Choice of climatic and soil regions is indicated and role of irrigation in such plantations is emphasized.